2018
DOI: 10.1371/journal.pone.0192235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dolomite and biochar addition on N2O and CO2 emissions from acidic tea field soil

Abstract: A laboratory study was conducted to study the effects of liming and different biochar amendments on N2O and CO2 emissions from acidic tea field soil. The first experiment was done with three different rates of N treatment; N 300 (300 kg N ha-1), N 600 (600 kg N ha-1) and N 900 (900 kg N ha-1) and four different rates of bamboo biochar amendment; 0%, 0.5%, 1% and 2% biochar. The second experiment was done with three different biochars at a rate of 2% (rice husk, sawdust, and bamboo) and a control and lime treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 52 publications
3
38
0
1
Order By: Relevance
“…This result was also supported by correlation analysis that N 2 O emission was inversely related with soil C/N ratio in this experiment ( Figure 7). Ernfors et al [44] and Oo et al [24] also reported that soil C/N ratio was negatively correlated with N 2 O emission, although no significant correlation was observed by Feng and Zhu [45]. Previous studies indicated that as the relative C content increases in soil, a higher proportion of ammonium is immobilized (or assimilated) by microbes instead of being nitrified (or mineralized), leading to a decrease in soil inorganic N and suppression of N 2 O emission [42].…”
Section: N 2 O Emissionsmentioning
confidence: 97%
See 3 more Smart Citations
“…This result was also supported by correlation analysis that N 2 O emission was inversely related with soil C/N ratio in this experiment ( Figure 7). Ernfors et al [44] and Oo et al [24] also reported that soil C/N ratio was negatively correlated with N 2 O emission, although no significant correlation was observed by Feng and Zhu [45]. Previous studies indicated that as the relative C content increases in soil, a higher proportion of ammonium is immobilized (or assimilated) by microbes instead of being nitrified (or mineralized), leading to a decrease in soil inorganic N and suppression of N 2 O emission [42].…”
Section: N 2 O Emissionsmentioning
confidence: 97%
“…Pruning residue of tea plants was about 4 t ha −1 in dry weight. Biochar was produced from carbonization of tea pruning residues under open fire using open burn kiln [24]. Pyrolysis temperature was approximately 500-600 • C and biochar yield was about 30% on a dry weight basis with this method.…”
Section: Soil and Biocharmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, biochar has received attention for possible use in agricultural soils. Conversion of crop residue into biochar and its application in soil as a soil amendment is a novel approach as a soil improver, as well as for carbon sequestration, improved soil fertility and crop production [15] and decreased greenhouse gas emission [16][17][18][19]. However, no difference or even an increase in soil N 2 O emissions after biochar application was observed in other studies [20,21].…”
Section: Introductionmentioning
confidence: 96%